Parametric Study on Microwave-Assisted Pyrolysis Combined KOH Activation of Oil Palm Male Flowers Derived Nanoporous Carbons - Napat Kaewtrakulchai; Kajornsak Faungnawakij; Apiluck Eiad-Ua (My University, 2020)
Oil palm male flowers (PMFs), an abundant agricultural waste from oil palm plantation in Thailand, have been utilized as an alternative precursor to develop nanoporous carbons (NPCs) via microwave-assisted pyrolysis combined potassium hydroxide (KOH) activation. The influences of relevant processing variables, such as activating agent ratio, microwave power, and activation time on the specific pore characteristics, surface morphology, and surface chemistry of PMFs derived nanoporous carbons (PMFCs) have been investigated to explore the optimum preparation condition. The optimum condition under a microwave radiation power of 700 W, activation holding time of 6 min, and activating agent ratio of 2:1 obtained the PMFC with the highest Brunauer-Emmett-Teller (BET) surface area and total pore volume approximately of 991 m2/g and 0.49 cm3/g, composed of a carbon content of 74.56%. Meanwhile, PMFCs have a highly microporous structure of about 71.12%. Moreover, activating agent ratio and microwave radiation power indicated a significant influence on the surface characteristics of PMFCs. This study revealed the potential of oil palm male flowers for the NPCs' production via microwave-assisted KOH activation with a short operating-time condition.
Keywords: Nanoporous; Adsorption and biosorption for pollutant removal